PENGARUH EKSTRAK LARUT AIR KAYU KUNING (Arcangelisia flava (L.) Merr.) TERHADAP FAGOSITOSIS MAKROFAG SECARA IN VITRO PADA TIKUS GALUR WISTAR - , DISCALUSI FLORENTINA, Prof. Dr. phil. nat. Sudarsono, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Yellow wood (Arcangelisia flava (L.) Merr.) is one of the Indonesia plant. Active compounds called berberin chloride can be found in this plant. This research was conducted to find out whether the extract of water-soluble yellow wood capable of influencing the activity of macrophage phagocytosis (the non-specific immune response), as well as what is the concentration of chloride in the extract of berberin arthritis activity of macrophage phagocytosis. Water soluble extract of yellow wood is divided into three test groups. Group I is the Group's treatment of water soluble extract of yellow wood levels of 1 mg/mL, group II with levels of 5 mg/mL, and group III with levels of 10 mg/mL, and there is a control group media. The macrophage cells taken from mouse peritoneal fluid strain Wistar were used to test the macrophage phagocytosis. Results of the index and the ratio of phagocytosis macrophages were evaluated with statistical tests with one-way ANOVA, 95% confidence level. The qualitative and quantitative were analyzed by Thin-Layer Chromatography (TLC). Results of the statistical analysis shows that the ratio parameters and index phagocytosis macrophages, just a test group III has significantly to media control, treatment groups I and II. While the result of the qualitative analysis of active compounds from water soluble extract of yellow wood suggests that the predominant compounds contained in the extract is berberine chloride. Thus, it can be concluded that the extract of water-soluble yellow wood (Arcangelisia flava (L.) Merr.) levels of 10 mg/mL have compounds berberine chloride of 0.14% (w/v) which affect the activity of phagocytosis macrophages.